2017
DOI: 10.1002/14651858.cd012776
|View full text |Cite
|
Sign up to set email alerts
|

Piperonyl butoxide (PBO) combined with pyrethroids in long-lasting insecticidal nets (LLINs) to prevent malaria in Africa

Abstract: Piperonyl butoxide (PBO) combined with pyrethroids in long-lasting insecticidal nets (LLINs) to prevent malaria in Africa (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Although PBO-pyrethroid nets are now replacing standard pyrethroid-only nets in many sites across Africa 8 , not all pyrethroid resistant populations can be effectively targeted by this synergist 8,9 as additional mechanisms are contributing to the resistance phenotype. Recently, using a meta-analysis approach of transcriptomic data from pyrethroid resistant An.…”
Section: Introductionmentioning
confidence: 99%
“…Although PBO-pyrethroid nets are now replacing standard pyrethroid-only nets in many sites across Africa 8 , not all pyrethroid resistant populations can be effectively targeted by this synergist 8,9 as additional mechanisms are contributing to the resistance phenotype. Recently, using a meta-analysis approach of transcriptomic data from pyrethroid resistant An.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrethroid-PBO net was given World Health Organisation (WHO) policy recommendation as a new class in 2017 based on epidemiological data from a cluster randomized trial in Muleba, Tanzania [21], which showed that Olyset Âź Plus LN (Sumitomo Chemicals Co. Ltd, Tokyo, Japan) reduced malaria-infection prevalence by 33% over 21 months of use compared to the standard LLIN, Olyset Âź Net, under a scenario of high pyrethroid resistance and net use. A recent Cochrane review predicted that PBO-pyrethroid LLIN is expected to be more effective in areas of moderate to high resistance mediated by metabolic resistance than in settings of low or no insecticide resistance [22].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the detoxifying and/or sequestering activities of cytochrome P450s, GSTs and Esterase have been associated with mosquitoes resistance to insecticides [20][21][22] . Piperonyl butoxide is a non-toxic synergist but has been proven to suppress DDT and Pyrethriods resistance in malaria vectors under laboratory conditions [23][24][25] . Likewise, in several endemic areas in sub-Saharan Africa, PBO incorporated into LLINs has also shown to be more efficacious and effective in controlling malaria vectors, thereby, reducing malaria incidence [26][27][28][29] .…”
mentioning
confidence: 99%